Mental health protection for healthcare workers in the SARS-COV2 pandemic - Galleguillos U., Tamara (Revista de Psiquiatría Clínica, 2022)
Healthcare workers in the SARS-COV2 pandemic have faced unprecedented stressors. International studies of the impact on Mental Health of epidemics and other disasters, place health workers as a risk group for the development of psychiatric symptoms. Recent research in countries that experienced the magnitude of the COVID-19 crisis before Latin America, show high levels of anguish, anxiety and depressive symptoms in health personnel, among others. There would be multiple risk factors, such as the fear of becoming ill or infecting others, poor working conditions and shortcomings in infection control strategies; in turn, greater experience, access to personal protective equipment, correct infection control procedures, and availability of psychological interventions would be protective factors. In Chile and in the rest of the world, measures have been taken for the mental well-being of the teams, however the evidence reveals that the most effective strategies are those that involve organizational changes and practical adaptations within the institutions. The role of team leaders and public policies that protect health workers are highlighted. There is, however, a dearth of models for providing evidence-based continuing psychological care. It cannot be postponed that society, and especially the authorities, become aware that protecting the mental health of health teams during and after the pandemic is a priority to correct the health and social crisis.